Antibiotic oxylipins from Alternanthera brasiliana and its endophytic bacteria. (February 2015) - Trapp, Marília Almeida; Kai, Marco; Mithöfer, Axel; Rodrigues-Filho, Edson
Graphical abstract: Seventeen oxylipins were identified as the antibiotic compounds from Alternanthera brasiliana . Endophytic bacteria isolated from this plant are also able to produce five of these compounds detected in plant tissues. It suggests that these oxylipins arise from an intriguing ecological relationship between this plant and its endophytic bacteria. Highlights: Oxylipins were identified as antibiotic compounds in Alternanthera brasiliana . Two oxylipins are reported as plant metabolites. These oxylipins seem to be related to endophytic bacteria. Endophytic bacteria isolated from A. brasiliana produce the same oxylipins. Abstract: Bioassay-guided fractionation of Alternanthera brasiliana stem extracts resulted in the isolation of an antibiotically active fraction. Five human pathogenic bacteria were used to guide the fractionation process for the isolation of antimicrobial compounds. Finally, 17 linoleate oxylipins were identified by LC–MS/MS and NMR spectroscopy. Five of the isolated compounds present in A. brasiliana tissues were also detected to be synthesized by endophytic bacteria of the genus Bacillus that were isolated from A. brasiliana . It is speculated that the antibiotic oxylipins from A. brasiliana might derive from bacteria and be involved in an ecological relationship between this plant and its endophytes.